DESIGN CENTRIFUGAL PUMP ASSISTED BY CF TURBO 10.2 SOFTWARE - Siprianus Ndaha Ate (TRANSMISI, 2019)
In the industrial world the use of centrifugal pumps is often used to distribute water that is to support the smooth running of industrial processes or to cool a machine. Centrifugal pumps have a very broad scope of use with the head and the resulting capacity is very large and varied. In this final project, a centrifugal pump with a capacity of 30 m3 / hour, a pump head of 10 meters, a shaft rotation of 1500 rpm and a pressure difference of 10 bar in and out is planned. In the planning of centrifugal pumps, CF Turbo 10.2 software is used. Fluid is water ("Water") with a temperature of 200 C. Specific gravity of 1 kg / dm3. The output of the software includes blade diameter, shape, number of blades and geometric representation of blades. In planning this centrifugal pump as a comparison material, the specifications of the centrifugal pump are available. 5-level centrifugal pump is planned, each level has a head of 10 meters, a discharge of 30 m3/hour.